Organic Light‐Emitting Transistors in a Smart‐Integrated System for Plasmonic‐Based Sensing. (1st August 2021) - Prosa, Mario; Benvenuti, Emilia; Kallweit, David; Pellacani, Paola; Toerker, Michael; Bolognesi, Margherita; Lopez‐Sanchez, Laura; Ragona, Vincenzo; Marabelli, Franco; Toffanin, Stefano
Abstract: The smart integration of multiple devices in a single functional unit is boosting the advent of compact optical sensors for on‐site analysis. Nevertheless, the development of miniaturized and cost‐effective plasmonic sensors is hampered by the strict angular constraints of the detection scheme, which are fulfilled through bulky optical components. Here, an ultracompact system for plasmonic‐sensing is demonstrated by the smart integration of an organic light‐emitting transistor (OLET), an organic photodiode (OPD), and a nanostructured plasmonic grating (NPG). The potential of OLETs, as planar multielectrode devices with inherent micrometer‐wide emission areas, offers the pioneer incorporation of an OPD onto the source electrode to obtain a monolithic photonic module endowed with light‐emitting and light‐detection characteristics at unprecedented lateral proximity of them. This approach enables the exploitation of the angle‐dependent sensing of the NPG in a miniaturized system based on low‐cost components, in which a reflective detection is enabled by the elegant fabrication of the NPG onto the encapsulation glass of the photonic module. The most effective layout of integration is unraveled by an advanced simulation tool, which allows obtaining an optics‐less plasmonic system able to perform a quantitative detection up to 10 −2 RIU at a sensor size as low as 0.1 cm 3 . Abstract : The angle‐dependent sensing characteristics of a nanostructured grating are enabled by an organic photonic device with unprecedented proximity of the light source and the light detection regions, provided by the smart integration of an organic photodiode onto a planar organic light‐emitting transistor. An advanced simulation tool allows unraveling the best layout of integration to obtain a miniaturized plasmonic sensor.